2007
DOI: 10.1523/jneurosci.1505-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Neurometabolic Coupling in the Lateral Geniculate Nucleus

Abstract: The relationships between neural and metabolic processes in activated brain regions are central to the interpretation of noninvasive imaging. To examine this relationship, we have used a specialized sensor to measure simultaneously tissue oxygen changes and neural activity in colocalized regions of the cat's lateral geniculate nucleus (LGN). Previous work with this sensor has shown that a decrease or increase in tissue oxygen can be elicited by selective control of the location and extent of neural activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 45 publications
(96 reference statements)
3
53
2
Order By: Relevance
“…This contradicts a sensory enhancement account in which attention acts to improve the discriminability of sensory signals. Compressive (or, equivalently, expansive if reported as the dependence of hemodynamic activity on electrophysiological activity) (Devor et al 2003;Li and Freeman 2007;Offenhauser et al 2005;Sheth et al 2004), linear (Arthurs et al 2000Ogawa et al 2000;Ngai et al 1999;Smith et al 2002). and threshold-linear relationships (Logothetis et al 2001;Schummers et al 2008) have been reported between optical measurements of hemodynamic activity and electrophysiology in numerous experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This contradicts a sensory enhancement account in which attention acts to improve the discriminability of sensory signals. Compressive (or, equivalently, expansive if reported as the dependence of hemodynamic activity on electrophysiological activity) (Devor et al 2003;Li and Freeman 2007;Offenhauser et al 2005;Sheth et al 2004), linear (Arthurs et al 2000Ogawa et al 2000;Ngai et al 1999;Smith et al 2002). and threshold-linear relationships (Logothetis et al 2001;Schummers et al 2008) have been reported between optical measurements of hemodynamic activity and electrophysiology in numerous experiments.…”
Section: Discussionmentioning
confidence: 99%
“…R. Soc. B 371: 20150357 the relative linearity of these variables [17,19]. To do this, visual stimuli with different durations and spatial patterns were presented, while activity from LGN cells was monitored.…”
Section: Temporal and Spatial Summationmentioning
confidence: 99%
“…This USPIO agent exhibits a long blood half-life (5-6 h in rat (Li and Freeman, 2007)), enabling CBV measurements to be made over a prolonged period following intravenous administration. CBV fMRI data sets were acquired using the same imaging paradigm as for the BOLD acquisition.…”
Section: Animal Preparationmentioning
confidence: 99%